2016
DOI: 10.1097/md.0000000000005516
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Th1 and Th17 cells infiltrate the intestinal mucosa of Behcet patients and exhibit high levels of TNF-α in early phases of the disease

Abstract: Background:Gastrointestinal involvement is one of the most serious in Behçet disease, potentially leading to severe complications. Aim of this study was to investigate at mucosal level the T-cell responses in Behçet patients with early intestinal involvement.Methods:We isolated T cells from intestinal mucosa of 8 patients with intestinal symptoms started within 6 months. T lymphocytes were cloned and analyzed for surface phenotype and cytokines production.Results:We obtained 382 T-cell clones: 324 were CD4+ an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 26 publications
5
36
0
Order By: Relevance
“…IL-18 positive cells were gated from ocular cells, and then 77.9% of IL-18 + cells were CD11b positive cells, in which the percentage of 33D1 + CD11b + CD11c + MHC-II + , 33D1 -CD11b + CD11c + MHC-II + , CD11b + F4/80 + Ly6c -, CD11b + F4/80 -Ly6c + , CD11b + F4/ 80 + Ly6c + were analysed. (D) With interphotoreceptor retinoid-binding protein peptide (IRBP)[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and pertussis toxin (PTX) stimulation or not, CD11c+DC, CD11c-depleted magnetic isolated CD45+ cells from the eyes of EAU mice and CD45+ cells without deletion were cultured for 48 h. Data show the basal production of IL-18 in the supernatants in non-stimulated CD45+ lymphocytes or after stimulation with IRBP 1-20 (10 ng/mL) and PTX (10 ng/mL) (data from three independent experiments, values represent the mean ± SEM, ANOVA test: ***P < 0.001) involves disorders of the immune system 1,2 with uveitogenic antigen-specific T cells serving as crucial effectors driving this disorder of the immune system to result in tissue damage 2,[48][49][50]. The severity of EAU is augmented by NK cells which were reported to play a pathological role in uveitis 3,4,[6][7][8][9].…”
mentioning
confidence: 99%
“…IL-18 positive cells were gated from ocular cells, and then 77.9% of IL-18 + cells were CD11b positive cells, in which the percentage of 33D1 + CD11b + CD11c + MHC-II + , 33D1 -CD11b + CD11c + MHC-II + , CD11b + F4/80 + Ly6c -, CD11b + F4/80 -Ly6c + , CD11b + F4/ 80 + Ly6c + were analysed. (D) With interphotoreceptor retinoid-binding protein peptide (IRBP)[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and pertussis toxin (PTX) stimulation or not, CD11c+DC, CD11c-depleted magnetic isolated CD45+ cells from the eyes of EAU mice and CD45+ cells without deletion were cultured for 48 h. Data show the basal production of IL-18 in the supernatants in non-stimulated CD45+ lymphocytes or after stimulation with IRBP 1-20 (10 ng/mL) and PTX (10 ng/mL) (data from three independent experiments, values represent the mean ± SEM, ANOVA test: ***P < 0.001) involves disorders of the immune system 1,2 with uveitogenic antigen-specific T cells serving as crucial effectors driving this disorder of the immune system to result in tissue damage 2,[48][49][50]. The severity of EAU is augmented by NK cells which were reported to play a pathological role in uveitis 3,4,[6][7][8][9].…”
mentioning
confidence: 99%
“…Butyrate is the preferred fuel for colonocytes and one of the most representative SCFA. It is able to induce T regulatory cell differentiation through several mechanisms, so butyrate impairment in BS individuals could promote reduced T regulatory cellmediated control, thus promoting a powerful immunopathological T cell response [8] as suggested by the higher percentage of Th1/Th17 cells in the intestinal mucosa observed in BS individuals [9]. The presence of an altered GM in BS individuals has recently been confirmed by Ye et al [29] These changes have been associated with altered biological microbial functions with an enhanced oxidation-reduction process, a capsular polysaccharide transport system, and type III and IV secretion systems [29].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, BS individuals showed a significant depletion of well-known butyrate producers, i.e. Roseburia and Subdoligranulum, and a consistent decrease in butyrate, one of the most representative short chain fatty acid (SCFA), thus suggesting an increase in the inflammatory state [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal involvement is an important complication of BD. Emmi et al [43] found that T cells at the intestinal mucosal level produce a high amount of TNF-α and in the early stage of BD. Both Th17 and Th1 cells drive inflammation and mucosal damage though long-lasting cytokine production [44].…”
Section: Entero-bdmentioning
confidence: 99%